Who, where, and why are patients lost to follow-up? A 20-year study of bladder exstrophy patients at a single institution. Issue 3 (June 2018) - Haddad, Emily; Sancaktutar, Ahmet Ali; Palmer, Blake W.; Aston, Christopher; Kropp, Bradley P.
Summary: Introduction: Individuals with bladder and cloacal exstrophy are at increased risk for kidney disease, renal failure, and bladder complications. Given the social implications and sensitive nature of the disease, these patients are also at risk for psychosocial problems. Lack of regular medical follow-up visits may pose serious risks to their long-term health status. The aim of this study is determine what factors place an affected individual at risk for limited long term follow up. Materials and methods: We identified all patients with bladder or cloacal exstrophy seen by the pediatric urology department at the Oklahoma University Health Sciences Center (OUHSC) between January 1996 and August 2016. Patient data included demographics, insurance coverage, distance from patient's home to the clinic, medical and surgical history, and the date of their last clinic visit. Two groups for comparison were (1) those that had been seen within the last 2 years, and (2) those that were counted as failing to maintain follow-up because 2 or more years had passed since their last clinic visit. These groups were compared using the Student t -test, the chi-square test, or the Fisher exact test and p  < 0.05 was treated as significant for the purposes of discussion. Results and discussion: Ninety-one patients with bladder or cloacal exstrophy were seen by the pediatric urology department between January 1996 and August 2016. Of the 91 patients, 24 left the clinic for known reasons thus leaving 67 patients that were considered for analyses: 51 had been seen within the last 2 years while 16 were counted as lost to follow-up. These two groups (active and lost to follow-up) did not differ significantly for age at last clinic visit, distance between family's home and clinic, history of bladder reconstruction, sex, or insurance status. There was a significant difference between the two groups in the medical complexity of their condition. The group active in urological care had more patients with cloacal exstrophy and additional anomalies than the group lost to follow-up. Conclusions: Patients with bladder exstrophy and cloacal exstrophy are less likely to maintain annual follow-up visits with their urologist if they have a simpler diagnosis requiring fewer surgical interventions. For patients with exstrophy, regular clinic visits prioritizing education and psychosocial support may prevent hospitalizations, emergency interventions, and poor overall health outcomes. To maintain contact with the medical team and promote optimal health outcomes, a social worker or care coordinator/educator may play an integral part in addressing the unique needs of this population.